Solidarity and Justice in Health Care. A Critical Analysis of their Relationship (Diametros, 2015)
This article tries to analyze the meaning and relevance of the concept of solidarity as compared to the concept of justice. While ‘justice’ refers to rights and duties (Moralität), the concept of solidarity refers to relations of personal commitment and recognition (Sittlichkeit). The article wants to answer the question whether solidarity and liberal justice should be seen as mutually exclusive or whether both approaches should be regarded as complementary to each other. The paper starts with an analysis of liberal theories of justice which are followed by an analysis of the descriptive and a moral understanding of the concept of solidarity. The importance of solidarity lies in its relational aspects, particularly its emphasis on cooperation and commonality. The paper argues that while solidarity is more fundamental than justice, both concepts are important for the arrangement of health care practices. The paper gives special attention to the concept of decent care, reflective solidarity and humanitarian solidarity which is seen as fundamental for all health care policies and care practices.